Comparison of pressure support and manual ventilation modes during anaesthesia emergence on postoperative atelectasis using lung ultrasonography: a prospective cohort study - Otlu Biyikoglu, Busra; Yurtlu, Bulent Serhan; Volkan Hanci; Ali Salih Biyikoglu (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the effects of different ventilatory approaches during the recovery phase of anaesthesia on the incidence of atelectasis. Method: The prospective cohort study was conducted from August to November 2022 at Dokuz Eylul University Hospital, Izmir, Turkiye, and comprised patients aged at least 18 years with an American Society of Anaesthesiologists physical status classification of I-III who were undergoing elective ophthalmic surgery, extremity surgeries, or septorhinoplasty procedures under general anaesthesia with endotracheal intubation for a duration of 1-3 hours. The patients were divided into pressure support ventilation group A and manual ventilation group B. Lung ultrasonography was performed preoperatively and postoperatively using a lung transthoracic ultrasound score system ranging 0-36. Degree of atelectasis in each lung region was rated on a 0-3 scale, and a total score was computed for every patient. Patients with a total score 0 were classified as having no atelectasis, while those with a score of 1 or higher were classified as having atelectasis. Data was analysed using SPSS 25. Results: Of the 2878 patients, 139(50%) were in group A; 72(51.8%) males and 67(48.2%) females with overall mean age 45.4±19.1 years. The remaining 139(50%) were in group B; 71(51.1%) males and 68(48.9%) females with overall mean age 49.7±18.6 years (p>0.05). The total postoperative lung ultrasonography median values were 1 (interquartile range: 0-3) in group A and 2(interquartile range: 0-4) in group B (p=0.041). Atelectasis was present in 106(76%) patients in group B compared to 84(60%) patients in group A (p=0.005). Conclusion: In patients who received pressure support ventilation, a lower incidence of postoperative atelectasis was observed, suggesting that pressure support ventilation may be a more effective ventilation method in the postoperative period. ClinicalTrials.gov ID: NCT06358027. Key Words: Lung ultrasonography, Atelectasis, Postoperative pulmonary complications, Pressure support ventilation, Lung ultrasound score.